PENGARUH PENDAMPINGAN SUAMI TERHADAP TINGKAT KECEMASAN IBU SELAMA PERSALINAN NORMAL - Endang Sari; Mekar Zenni Radhia (Ensiklopedia of Journal, 2025)
Abstract: Childbirth is an event that can trigger anxiety.. Several efforts can be made to reduce anxiety during childbirth, namely by caring for the mother and baby with the principle of including the husband and family during the birth process. The aim of this research is to see the influence of the husband's assistance on the mother's level of anxiety facing childbirth.This research method uses Pre Experimental with a One Group Pretest-Posttest Design design. The population in this study was mothers in the 1st stage of labor totaling 30 mothers divided into 2, namely 1 control group and 1 intervention group. The sampling technique is total sampling. Data was collected using a questionnaire. The intervention was carried out with the husband's assistance. Data analysis was carried out univariate and bivariate using the Pired sample T-test.The results of the research showed that the frequency distribution of anxiety among mothers who were accompanied by their husbands was mostly in the not anxious category, 11 (73.3%) and the anxiety of mothers in the unaccompanied group was mostly in the mild anxiety category, namely 7 people (47.7%). Based on the results of statistical tests, there is an influence of husband's assistance on maternal anxiety, namely p value = 0.000 ( 0.05).The conclusion of this research shows that there is an influence of husband's assistance on maternal anxiety. It is recommended that health workers carry out an alert care program for mothers and husbands.Keywords: Husband's Accompaniment, Mother's Anxiety Level in Birth.